Effect of anaerobic power on agility and quickness in male national taekwondo athletes - Taskin, M.; Akkoyunlu, Y. (Kinesiologia Slovenica, 2020)
The aim of this study was to determine the effect on anaerobic power on agility and quickness male national taekwondo athletes. The sample included 16 national male taekwondo athletes. These taekwondo athletes were from Turkey male national team. Athletes characteristics were as follows: age = 21.81 ± 3.229 years, height = 1.82 ± 0.088 m, body weight = 73.75 ± 14.187 kg, and sport age = 11.94 ± 3.454 years. To determine the quickness and agility performance of taekwondo athletes, a 5-m quickness test and T test was used. Wingate anaerobic test was used for anaerobic power. There is no a significantly relationship between agility with anaerobic peak power (w) and anaerobic power mean (w). There is a significantly relationship between agility with anaerobic peak power (w.kg-1) and anaerobic peak power mean (w.kg-1). Anaerobic peak power (w.kg-1) and anaerobic peak power mean (w.kg-1) in a unit change affect agility performance (respectively, -0.23 and -0.34 rate) (P<0.05). There is a significantly relationship between quickness with anaerobic peak power (w) and anaerobic peak power mean (w). Anaerobic peak power (w) and anaerobic peak power mean (w) in a unit change affects quickness performance (respectively, 0.0004 and 0.0001 rate) (P<0.05). There is no a significantly relationship between quickness with anaerobic peak power (w.kg-1) and anaerobic peak power (w.kg-1).In conclusion, this results have reported that male taekwondo athletes produce a high level of power during a short momentary situation and relative power is more important in momentary change of direction when the distance increases.